N-pyridinyl sulfilimines as a source for α-imino gold carbenes: access to 2-amino-substituted N-fused imidazoles - Tian, Xianhai; Song, Lina; Rudolph, Matthias; Wang, Qian; Song, Xinlong; Rominger, Frank; Hashmi, A. Stephen K. (Organic letters, 2019)
Gold-catalyzed formal 1,3-dipolar annulation between readily accessible N-pyridinylsulfilimines and ynamides is reported. A diverse set of imidazole derivatives is prepared from the corresponding sulfilimines and ynamides. These functionalized cyclic products can undergo further transformations to afford diverse imidazole frameworks. Moreover, in situ synthesis is feasible and shows good potential in the synthesis of nucleoside analogues.
Gesehen am 16.07.2019